CFD simulation of gas-liquid flows in a reactor stirred by dual rushton turbines - Kasat, Gopal R.; Pandit, Aniruddha B.; Ranade, V. V. (International Journal of Chemical Reactor Engineering, 2008)
In the present work, we have simulated gas-liquid flows in a tall stirred reactor equipped with dual Rushton turbines. A two fluid model along with the standard k-epsilon turbulence model and modified drag coefficient, (proposed by Khopkar & Ranade, 2006) accounting for the effect of bulk turbulence, was used to simulate the dispersed gas-liquid flow in a stirred reactor. The multiple reference frames (MRF) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc. USA). The model was used to simulate three distinct flow regimes in a gas-liquid stirred reactor: L33-VC (lower impeller-upper impeller), S33-VC and VC-VC. The model predictions were compared with the published experimental data of Bombac & Zun (2000). The predicted results show good agreement with the experimental data for all the three flow regimes. The computational model presented in this work would be useful for simulating different flow regimes in a gas-liquid stirred vessel.
Keywords: computational fluid dynamics; dual Rushton turbine; Flow regimes; gas hold-up distribution; stirred reactor

Crystal shape evolution using polyhedral population balance - Shaikh, Latif J.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2014)
Research on crystal morphology covers shape evolution of single crystal and evolution of the size and shape distribution of populations of crystals. The population balance models have been used for the single or multiple dimensions for predicting the evolution of crystal size distributions (CSDs). More often than not these models do not consider the change in solute concentration due to disappearance/appearance of the crystal faces and therefore compromise rigorous mass balance. The present work focuses on the methodology for the morphological evolution of crystal shape using a polyhedral population balance model. This methodology is based on the morphodrome which illustrates the shapes of crystals at various operating conditions. gPROMS software (PSE, UK) along with Microsoft Excel is used to devise the framework for predicting the crystal shape evolution. The developed approach and models can be implemented for various crystallization systems and will be useful for simulating crystal shape evolutions.